1987
DOI: 10.1104/pp.85.1.224
|View full text |Cite
|
Sign up to set email alerts
|

Water Binding in Legume Seeds

Abstract: The physical status of water in seeds has a pivotal role in determining the A large proportion of Angiosperm seeds are orthodox in that they can survive desiccation. As desiccation of these seeds proceeds there is no evidence of large structural changes in their membranes (15,19,23) and it has been suggested that the lack of major conformational changes in membranes upon drying is an essential characteristic of desiccation tolerance (5, 13).Because there are limited structural changes induced by the addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
69
2
4

Year Published

1994
1994
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(83 citation statements)
references
References 17 publications
8
69
2
4
Order By: Relevance
“…In the present study, the isotherms for T. superba, T. ivorensis, E. angolense, K. anthotheca and M. altissima are consistent with those of native species of Australia generated by Merritt et al (2003). They exhibited a reverse sigmoidal shape characteristic of orthodox species as reported by McDonald & Copeland (1996), but they varied from species to species due to differences in composition (Vertucci & Leopold, 1987;Vertucci & Roos, 1993). The curves have inflection points at approximately 13-25% RH for the boundary of sorption zones 1 and 2, and another at 60-80% RH for the boundary of sorption zones 2 and 3 at 20 °C.…”
Section: Water Sorption In G Kola Seedssupporting
confidence: 90%
See 2 more Smart Citations
“…In the present study, the isotherms for T. superba, T. ivorensis, E. angolense, K. anthotheca and M. altissima are consistent with those of native species of Australia generated by Merritt et al (2003). They exhibited a reverse sigmoidal shape characteristic of orthodox species as reported by McDonald & Copeland (1996), but they varied from species to species due to differences in composition (Vertucci & Leopold, 1987;Vertucci & Roos, 1993). The curves have inflection points at approximately 13-25% RH for the boundary of sorption zones 1 and 2, and another at 60-80% RH for the boundary of sorption zones 2 and 3 at 20 °C.…”
Section: Water Sorption In G Kola Seedssupporting
confidence: 90%
“…Desiccation intolerant species have the monotonic shaped or a simple rising curve (Vertucci & Leopold 1987;Eira et al, 1999). Eira et al (1999) have reported that the shape of isotherms of coffee seed tissues was intermediate to the reverse sigmoidal shape observed for orthodox seeds and the monotonic shape observed for desiccation intolerant plant tissues.…”
Section: Water Sorption Isotherm Characteristics Of Seeds Of Six Indimentioning
confidence: 99%
See 1 more Smart Citation
“…Sorption and desorption isotherms were similar for the cultivars; however the cultivar Mulato 1 revealed different A w values on the extreme mc (Figure 2). The isotherms displayed consist of three regions, located at low, intermediate and high mc levels (Vertucci and Leopold, 1987).…”
Section: Resultsmentioning
confidence: 99%
“…The isotherm obtained consists of three regions: one, at low moisture contents, in which moisture rises steeply for a small increase in RH (water sorption at strong binding sites); a second region, at intermediate moisture contents, in which the gradient is shallow (water sorption at weak binding sites) and a third region, at high moisture contents, in which moisture increases again more steeply for a small increase in RH (water sorption binding to already absorbed water molecules) (Vertucci & Leopold, 1987). Similar results have been recorded by Barker & Laird (1997), during moisture sorption/desorption experiments, using gin run cottonseeds, kept at 20°C.…”
Section: Resultsmentioning
confidence: 99%